2010
DOI: 10.1089/dna.2009.0993
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Arginines in the Mode of Binding of H1 Histones to DNA

Abstract: The mode of binding of sperm and somatic H1 histones to DNA has been investigated by analyzing the effect of their addition on the electrophoretic mobility of linear and circular plasmid molecules. Low concentrations of sperm histones do not appear to alter the electrophoretic mobility of DNA, whereas at increasing concentrations, an additional DNA band is observed near the migration origin. This band then becomes the only component at higher values. In contrast, somatic histones cause a gradual retardation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
8
19
0
Order By: Relevance
“…This suggested that hyposalinity exposure did not affect DNA binding mode of PL proteins, different from what we have seen while exposing mussels to copper chloride . In that case, we observed an increase in DNA binding affinity and also a change of DNA binding mode from "all or nothing" to "intermediate mode", the typical DNA binding mode of somatic H1 histone (Piscopo et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This suggested that hyposalinity exposure did not affect DNA binding mode of PL proteins, different from what we have seen while exposing mussels to copper chloride . In that case, we observed an increase in DNA binding affinity and also a change of DNA binding mode from "all or nothing" to "intermediate mode", the typical DNA binding mode of somatic H1 histone (Piscopo et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…galloprovincialis spermatozoa and on protamine‐like proteins (PL‐ proteins). These proteins are related to histone H1 and are rich in arginine and lysine (30–50 mol%; Fioretti et al, ; Piscopo et al, ). They represent the 76% of the overall nuclear protein in M .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nothing has been presented to date on the bactericidal activity of protamine-like proteins (PL-proteins), which are one of the three types of Sperm Nuclear Basic Proteins (SNBPs) and represent a structurally and functionally intermediate group of proteins between the histone (H) and protamine (P) type (Ausió, 1999). These proteins are related to histone H1 and are arginine-and lysine-rich Piscopo et al, 2010). They were first described in bivalve mollusks but later have been also found in echinoderms, tunicates, and vertebrates (Ausió, 1995;Eirin-Lo´pez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the on-dyad axis location creates more compacted (transcriptionally inert) chromatin conformation, the off-dyad axis position forms more loosened (transcriptionally capable) chromatin structure (Zhou et al, 2015). Moreover, the mode of histone H1 binding to the DNA is determined by its C-terminal (Th'ng et al, 2005) and globular (Piscopo et al, 2010) domain and may be different in distinct cell types. Due to the presence of the arginine residues, the sperm H1-like histones are able to form aggregates and highly condensed DNA in comparison to the somatic H1 histones deprived of arginine and are thus unable to selfassociate and create highly packaged DNA (Salvati et al, 2008).…”
Section: Introductionmentioning
confidence: 99%